2019
DOI: 10.1093/cvr/cvz310
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the molecular and histological events that govern right ventricular recovery using a novel mouse model of pulmonary artery de-banding

Abstract: AIMS The temporal sequence of events underlying functional right ventricular (RV) recovery after improvement of pulmonary hypertension-associated pressure overload are unknown. We sought to establish a novel mouse model of gradual RV recovery from pressure overload and use it to delineate RV reverse-remodeling events. METHODS AND RESULTS Surgical pulmonary artery banding (PAB) around a 26G needle induced RV dysfunction with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 32 publications
6
27
0
Order By: Relevance
“…In addition to reductions in forced high intensity exercise (Piao et al, 2012) and voluntary low intensity exercise (Borgdorff et al, 2012(Borgdorff et al, , 2013b, inactivity, reduced grooming, dyspnea/tachypnea, poor peripheral circulation, ascites and pleural/pericardial effusions have been reported, culminating in a high mortality rate (LekanneDeprez et al, 1998;Schou et al, 2007;Borgdorff et al, 2013bBorgdorff et al, , 2015b. These pathological changes have also been replicated in mice (Urashima et al, 2008;Kapur et al, 2013;Egemnazarov et al, 2015;Boehm et al, 2017Boehm et al, , 2020.…”
Section: Pulmonary Artery Bandingmentioning
confidence: 95%
“…In addition to reductions in forced high intensity exercise (Piao et al, 2012) and voluntary low intensity exercise (Borgdorff et al, 2012(Borgdorff et al, , 2013b, inactivity, reduced grooming, dyspnea/tachypnea, poor peripheral circulation, ascites and pleural/pericardial effusions have been reported, culminating in a high mortality rate (LekanneDeprez et al, 1998;Schou et al, 2007;Borgdorff et al, 2013bBorgdorff et al, , 2015b. These pathological changes have also been replicated in mice (Urashima et al, 2008;Kapur et al, 2013;Egemnazarov et al, 2015;Boehm et al, 2017Boehm et al, , 2020.…”
Section: Pulmonary Artery Bandingmentioning
confidence: 95%
“…However, multiple preclinical drug studies show reduction in RV fibrosis is associated with improved RV function, but all occur in the setting of reduced afterload ( 65 , 66 , 67 , 68 , 69 ). Furthermore, a novel pulmonary artery debanding mouse model shows that, after pulmonary artery band resorption, RV function is restored with normalization of cardiomyocyte size and reversal of fibrosis ( 70 ).…”
Section: Mechanisms Of Rv Dysfunction In Pahmentioning
confidence: 99%
“…rats with monocrotaline-induced PH, rabbits with shunt flow-induced PH) have shown that exogenous HGF or Hgf gene transfection reduced the development of PH, which was associated with less marked right heart hypertrophy and lower inflammatory profiles than shams (27–30). However, the timely and direct effect of the HGF/c-Met axis activation in the right heart remains to be elucidated, and here the PAB model might be of particular value to explore the dynamic changes in plasma and tissue HGF expression over time and potential reversibility with de-banding (10).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic RV pressure overload was induced in 10-14 week-old male C57BL/6 mice ( Supplementary Methods ) (10). Anesthetized animals underwent thoracotomy, 6-0 silk sutures were used to band the main pulmonary artery (PA), and one-week post-surgery a peak pressure gradient >15 mmHg was confirmed across the band by echocardiography (GE Vivid 7).…”
Section: Methodsmentioning
confidence: 99%